2017
DOI: 10.1021/acs.orglett.6b03276
|View full text |Cite
|
Sign up to set email alerts
|

Lewis Acid Catalyzed Diastereoselective Cycloaddition Reactions of Donor–Acceptor Cyclopropanes and Vinyl Azides: Synthesis of Functionalized Azidocyclopentane and Tetrahydropyridine Derivatives

Abstract: Lewis acid catalyzed [3 + 2]-cycloaddition reaction of donor-acceptor cyclopropanes with vinyl azides has been developed to obtain diastereomerically enriched azidocyclopentane derivatives. In addition, thermal chemoselective ring expansion of azidocyclopentanes to tetrahydropyridine derivatives and further diastereospecific reduction to a substituted piperidine derivative, with an excellent yield, was also achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 107 publications
(23 citation statements)
references
References 31 publications
0
17
0
3
Order By: Relevance
“…Keywords iodine catalysis; vinyl azide; free radical addition; sulfonyl enamine 乙烯基叠氮化合物 [1][2][3] 是同时具有双键和叠氮基团 的分子, 该类分子由 Forster 和 Newman [4] 首次提出并报 道, 到现在已经有近一百年的历史 [5][6] . 其拥有单独的烯 烃或叠氮基结构所没有的独特性质, 它可以作为亲电试 剂 [7][8] 、亲核试剂 [9][10][11][12][13] 或自由基受体 [14][15][16][17][18][19] 等, 同时能够通 过多种反应途径生成各类高反应活性的中间体 [20] , 因 此这类化合物在有机合成方面具有非常重要的作用. 在 过去的十几年中, 乙烯基叠氮化合物得到了很好的发 展, 这也是由于过渡金属催化的强大推动力以及实际制 备方法的最新发展所致.…”
unclassified
“…Keywords iodine catalysis; vinyl azide; free radical addition; sulfonyl enamine 乙烯基叠氮化合物 [1][2][3] 是同时具有双键和叠氮基团 的分子, 该类分子由 Forster 和 Newman [4] 首次提出并报 道, 到现在已经有近一百年的历史 [5][6] . 其拥有单独的烯 烃或叠氮基结构所没有的独特性质, 它可以作为亲电试 剂 [7][8] 、亲核试剂 [9][10][11][12][13] 或自由基受体 [14][15][16][17][18][19] 等, 同时能够通 过多种反应途径生成各类高反应活性的中间体 [20] , 因 此这类化合物在有机合成方面具有非常重要的作用. 在 过去的十几年中, 乙烯基叠氮化合物得到了很好的发 展, 这也是由于过渡金属催化的强大推动力以及实际制 备方法的最新发展所致.…”
unclassified
“…This reaction did not require any reagent and did not produce any by‐product. The scope and limitation of this cycloaddition reaction were explored with various DACs and vinyl azides and it was found that the desired product was obtained in good to excellent yield with a high diastereoselective ratio …”
Section: Synthesis Of Six‐membered Nitrogen Heterocyclesmentioning
confidence: 99%
“…Reports by Johnson, Wang, and other groups demonstrated that various 2π-components react with DACs to afford a wide range of carbocycles and heterocycles . Our group has also explored the cycloaddition and annulation reactions of DACs with epoxides, aziridines, oxaziridines, nitrosocarbonyls, enamines, and vinyl azides for the synthesis of carbocyles and heterocycles relevant to biological applications . In 2009, Kerr et al reported a notable approach to assemble tetrahydrocarbazoles, which involved ring opening of DACs with indole and Conia-ene cyclization .…”
mentioning
confidence: 99%